Resistências nas discussões de gênero, sexualidade e educação como efeitos de discursos (neo) conservadores - VILHENA, Raquel Xavier (2023)
This article aims to analyze the conservative alliance in Brazil and its attacks on education in the face of gender and sexuality debates. As well as the articulation of the religious bench in order to engage sympathizers and conquer more and more space in the school. We can highlight among them the campaign against the so-called “gender ideology”. In addition, the removal of the words “gender identity” and “sexual orientation” in discussions about the national common curriculum base (BNCC) Proposals that focus on discussions regarding diversity (gender and sexuality) in addition to attacks on education, o it generates restrictions in the performance of teachers and in the construction of a more democratic and pluralistic school. From this context, this article aims to highlight not only these educational reforms in their relationship with the social, political, and cultural context, but also analyzing their consequences at school. For this, a theoretical bibliographic research was carried out, as well as the analysis of (BNCC), and processes of resistance to these discourses.